Enantioselective Construction of Bispirooxindoles via Squaramide‐Catalysed Cascade Michael/Cyclization Reaction - Zhao, Bo‐Liang; Lin, Ye; Du, Da‐Ming (Advanced synthesis & catalysis, 2019)
A series of readily available 2‐(2‐oxoindolin‐3‐yl)malononitriles bearing multiple active sites were first used in asymmetric catalytic synthesis, which have been successfully applied to develop a bifunctional squaramide‐catalyzed cascade Michael/cyclization reaction strategy. Various cyclopentene‐bispirooxindoles with three continuous stereocenters, two of which are quaternary spiro‐stereocenters, were constructed in good yields with excellent stereoselectivities (up to >20:1 dr, >99% ee).